2005
DOI: 10.1002/jip.19
|View full text |Cite
|
Sign up to set email alerts
|

Motivational sources of confirmation bias in criminal investigations: the need for cognitive closure

Abstract: In two experiments, criminal investigators (N = 50)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(188 citation statements)
references
References 32 publications
5
177
1
5
Order By: Relevance
“…NFCC refers to individuals' preference for unambiguity, with those assessed with a high need being characterised by a tendency to form quick judgements based on a solitary hypothesis, despite inconclusive evidence, while avoiding others' dissenting viewpoints (Kruglanski and Webster 1996). While Ask and Granhag (2005) did not find confirmation bias linked to NFCC among investigators, the current study examined whether NFCC is associated with insufficient planning.…”
Section: Theoretical Framework Of Investigative Interview Planningmentioning
confidence: 78%
See 2 more Smart Citations
“…NFCC refers to individuals' preference for unambiguity, with those assessed with a high need being characterised by a tendency to form quick judgements based on a solitary hypothesis, despite inconclusive evidence, while avoiding others' dissenting viewpoints (Kruglanski and Webster 1996). While Ask and Granhag (2005) did not find confirmation bias linked to NFCC among investigators, the current study examined whether NFCC is associated with insufficient planning.…”
Section: Theoretical Framework Of Investigative Interview Planningmentioning
confidence: 78%
“…Indeed, other research (which also employed similar limited predictors) also found non-significant outcomes (O'Neill 2011). Ask and Granhag (2005) also found that NFCC did not significantly affect bias in investigative decision-making. As these authors recommend, a more valid test of this disposition might be needed.…”
Section: Study Limitationsmentioning
confidence: 82%
See 1 more Smart Citation
“…Suggestive interviewing is strongly related to the concept of interviewer bias and the expectancy effects that emerge when interviewers with preconceived notions seek to confirm evidence in ways that are related to a priori beliefs and expectations (e.g. Ask and Granhag 2005;Bruck et al 2002). Children may, for example, tailor their reports by confirming or rejecting information if they infer that interviewers would prefer certain responses (e.g.…”
Section: Suggestive Interviewingmentioning
confidence: 99%
“…However, for the most part, serial killers are inclined to victimize population sectors they deem unworthy of living, largely because of abuse they experienced in childhood. Therefore, analyzing the victims at the crime scene can give the profiler a foundation for understanding the motive [29]. …”
mentioning
confidence: 99%